Nickel‐Catalyzed Cross‐Coupling of Redox‐Active Esters with Boronic Acids. (6th July 2016) - Wang, Jie; Qin, Tian; Chen, Tie‐Gen; Wimmer, Laurin; Edwards, Jacob T.; Cornella, Josep; Vokits, Benjamin; Shaw, Scott A.; Baran, Phil S.
Abstract: A transformation analogous in simplicity and functional group tolerance to the venerable Suzuki cross‐coupling between alkyl‐carboxylic acids and boronic acids is described. This Ni‐catalyzed reaction relies upon the activation of alkyl carboxylic acids as their redox‐active ester derivatives, specifically N ‐hydroxy‐tetrachlorophthalimide (TCNHPI), and proceeds in a practical and scalable fashion. The inexpensive nature of the reaction components (NiCl2 ⋅6 H2 O—$9.5 mol −1, Et3 N) coupled to the virtually unlimited commercial catalog of available starting materials bodes well for its rapid adoption.